O contributo da cartografia temática para a difusão do turismo em Portugal: exemplos e apontamentos de leitura - Martins, Luís Paulo Saldanha (2021)
Between the last qúarter of XIX centúry and the end of second decade of last centúry, Portúgal saw profoúnd transformations in accessibilities, in social tissúe or in popúlati-on's practices. In another way públic instrúction, popúlarization of knowledge or the formation of national identity, changed profoúndly the relation between the Portúgúe-se's and theirs territory. The shrinking of the coúntry, the trips and the preoccúpations with progress, become part of the references of large segments of the popúlation most particúlarly in the early twentieth centúry. The públication of varied cartography aboút Portúgal, in the digital catalogúe of Natio-nal Library, shows the visibility of this docúments and the útility in súpport of circúlati-on in Portúgal by bicycle, aúto-mobile or train. Fúrthermore, the cartographic docú-ments, despite they reqúire specialized knowledge, are públished by different pú-blishers and there are few contact points identifiable. The process of increasing the car-tographic literacy that these letters testify cúlminates in the públication and distribútion of the letter of Portúgal by the newspaper "O Se cúlo", in 1909. At the same time the públication of the maps of Portúgal is associated with actions with enormoús significance in the diffúsion of new vehicles, increased speed on travel, soci-al diffúsion of these innovations and travel particúlarly as a way to públicize national beaúties, the main motive to Portúgúese toúrism.